Pengaruh Beban Kerja, Motivasi Kerja, dan Disiplin Kerja Terhadap Kinerja Pegawai di Pusat Sumber Daya Mineral Batubara dan Panas Bumi (PSDMBP) - Yusmayanti Nur Muthmainah; Dedi Gumilar (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study seeks to understand how  workload, work motivation, and work discipline affect employee performance at PSDMBP. A quantitative approach was supported by descriptive analysis and verification. Out of 171 employees, the researcher chose 64 individuals using the Simple Random Sampling  method. The information gathered from the survey  was analyzed using multiple linear regression with the assistance of SPSS version 27. The analytical procedure comprised descriptive analysis, hypothesis testing, and determination coefficient. A summary of the data, validation of the study hypothesis, and disclosure of the degree of correlation between variables were the goals of this analysis. The findings reveal that workload and work motivation do not have a significant effect on employee performance. In contrast, work discipline has a significant influence. Simultaneously, workload, work motivation, and work discipline contribute 76.4% to employee performance.